MAQASHID SHARIA AND CUSTOMER DECISIONS IN ISLAMIC HOUSING FINANCE: EVIDENCE FROM WEST JAVA - Ramadhan, Fajri Haykal; Ismal, Rifky (Finansha: Journal of Sharia Financial Management, 2024)
The purpose of this study is to analyze Maqashid Sharia, specifically dharuriyat (necessities) proxied by service quality, hajiat (complementary needs) proxied by location, and tahsiniyat (embellishments) proxied by promotion, on customer decisions within the FLPP program in Islamic banking in West Java. This study adopts a quantitative research approach. Primary data were collected through a structured questionnaire, with the sampling technique employed being purposive sampling. The sample size consists of 100 customers of BJB Syariah and BTN Syariah involved in the FLPP (Housing Financing Liquidity Facility) program in West Java. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM).The study concludes that the variables dharuriyat, hajiat, and tahsiniyat significantly influence customer decisions in the FLPP program, accounting for 75.5% of the decision-making process, categorized as strong. Among these, the dharuriyat variable, represented by service quality, has the highest impact, contributing 72.5%. The findings imply that customers' decisions to secure a home through the FLPP program are primarily driven by their housing needs rather than investment motives. In contrast, the tahsiniyat variable, represented by promotion, exhibits the lowest impact at 21%. This outcome indicates that tahsiniyat elements, which enhance the aesthetic and convenience aspects of life, are not critical to fulfilling essential or complementary needs (dharuriyat and hajiat). Thus, their absence does not pose significant difficulties or threats to these core elements.